Indelible Math Moments (pp. 19–22) - Edwards, Michael Todd (Ohio Journal of School Mathematics, 2020)
The author discusses “indelible moments,” a writing activity that can be used in any classroom to foster positive community relationships and understanding. As students engage in the activity, they write about important mathematical moments—ones that have been so instrumental that they can’t be forgotten—then share them with classmates. The author shares a personal moment as an example.